Digital financial inclusion and rural income convergence in China: Evidence from household panel data - Jue Yu; Bohong Wu (PLoS ONE, 2026)
The rapid expansion of digital financial inclusion (DFI) in China has raised concerns that a rural-urban “digital divide” could worsen income inequality. Using 55,684 household-year observations from the China Family Panel Studies (2012−2022) combined with a provincial DFI index, we investigate whether DFI expansion helps rural households catch up or leaves them further behind. DFI is a significant driver of rural income growth. A one-standard-deviation increase in the DFI index raises per capita household income by 4.6%. Importantly, we find evidence of income convergence rather than divergence, as DFI benefits extend to both the bottom-40% and top-20% of income earners. However, these benefits are not evenly distributed. The positive effects of DFI are significantly stronger for households in more developed areas, those with higher education levels, and those headed by males. Mediation analysis reveals that DFI’s income effects operate through multiple complementary channels: while improved financial inclusion (asset ownership and credit access) plays a significant role, the majority of benefits flow through alternative pathways including e-commerce participation, reduced transaction costs for remittances, access to market information, and digital network effects. While DFI helps narrow the primary urban-rural gap, our findings highlight a new “digital-within-digital” divide. Policies promoting digital literacy and infrastructure in inland regions are crucial to prevent some rural subgroups from being left behind and to ensure equitable growth.